Chemical fuel-driven transient polymeric micelle nanoreactors toward reversible trapping and reaction acceleration. Issue 47 (17th May 2021) - Lang, Xianhua; Thumu, Udayabhaskararao; Yuan, Ling; Zheng, Chengrui; Zhang, Huajun; He, Lirong; Zhao, Hui; Zhao, Changsheng
Abstract : Chemical fuels tune the assembly and dissipative processes of polymeric micelle nanoreactors to overcome product inhibition issues. Abstract : In most synthetic nanoreactor systems, catalysed products do not promptly diffuse away from the nanoreactor, which leads to lower than expected catalytic efficiencies. To address the diffusion problem, transient polymer micelle nanoreactor systems were achieved using 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC) as the fuel and activated esters as the energy dissipating units. These demonstrated pathway-dependent catalytic properties for transient micelles: product inhibition was observed or efficiently eliminated depending on EDC reloading in the metastable stage or after full dissipation for transient micelles.